2016
DOI: 10.1002/aic.15497
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of homogeneous 5‐hydroxymethylfurfural oxidation to 2,5‐furandicarboxylic acid with Co/Mn/Br catalyst

Abstract: 2,5‐furandicarboxylic acid (FDCA) is a potential non‐phthalate based bio‐renewable substitute for terephthalic acid‐based plastics. Herein, we present an investigation of the oxidation rate of 5‐hydroxymethylfurfural (HMF) to FDCA in acetic acid medium using Co/Mn/Br catalyst. Transient concentration profiles of the reactant (HMF), intermediates [2,5‐diformylfuran (DFF), 5‐formyl‐2‐furancarboxylic acid (FFCA)], and the desired product (FDCA) were obtained for this relatively fast reaction in a stirred semi‐bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 41 publications
4
66
0
Order By: Relevance
“…Some studies reported the oxidation of 5‐hydroxymethylfurfural (HMF), a promising biobased platform chemical derived from sugars, 12 with Co/Mn/Br catalyst in acetic acid 8,13,14 . These were performed in a semi‐batch reactor with an upward bubbly flow at atmospheric pressure, 8 or in (fed‐)batch autoclaves under elevated pressures/temperatures with a gas‐inducing impeller by which oxygen bubbles were generated in the liquid phase through a sparger 13,14 . This resulted in 2,5‐diformylfuran (DFF) and 2,5‐furandicarboxylic acid (FDCA) that find potential applications in, for example, resins, pharmaceuticals, or as polymer building blocks 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported the oxidation of 5‐hydroxymethylfurfural (HMF), a promising biobased platform chemical derived from sugars, 12 with Co/Mn/Br catalyst in acetic acid 8,13,14 . These were performed in a semi‐batch reactor with an upward bubbly flow at atmospheric pressure, 8 or in (fed‐)batch autoclaves under elevated pressures/temperatures with a gas‐inducing impeller by which oxygen bubbles were generated in the liquid phase through a sparger 13,14 . This resulted in 2,5‐diformylfuran (DFF) and 2,5‐furandicarboxylic acid (FDCA) that find potential applications in, for example, resins, pharmaceuticals, or as polymer building blocks 15 .…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in 2,5‐diformylfuran (DFF) and 2,5‐furandicarboxylic acid (FDCA) that find potential applications in, for example, resins, pharmaceuticals, or as polymer building blocks 15 . In a fed‐batch reactor operated at elevated pressures and temperatures, the FDCA formation rate was limited by the gas–liquid mass transfer as shown by the notable influence of stirring rate on the reaction performance 14 . Also the oxidation of lignin, a major polymeric component in biomass, was performed with Co/Mn/Zr/Br catalysts in acetic acid 16 .…”
Section: Introductionmentioning
confidence: 99%
“…As reported, furan ring outperforms benzene ring and cyclohexane ring in many aspects while being used as a building block for polymers because of its improved barrier properties for oxygen, carbon dioxide, and water vapor as well as better thermal stability and mechanical properties. [21][22][23] It is therefore rational that the amination product of HMF, that is, 2,5-bisaminomethylfuran (BAMF), would be an outstanding monomer for amine-containing polymers such as polyurethane and polyamide. [24,25] However, simultaneous reductive amination of C=O and CÀ OH in HMF into CÀ NH 2 in BAMF seems much challenging so as it has seldom been reported until today.…”
mentioning
confidence: 99%
“…However, the FDCA selectivities of these systems were low. Although a recent report claimed approximately 95 % FDCA yield by using a Co/Mn/Br catalytic system through optimization of reaction conditions to minimize the complete oxidation of substrate into carbon oxides and other side reactions, corrosive media (e.g., acetic acid) must be used, which makes the process less green . Strong bases (e.g., NaOH, NaH) have been reported to promote the oxidative conversion of HMF in dimethylformamide solvent, but the problems of product isolation remain …”
Section: Conversion Of Cellulose Into Dicarboxylic Acidsmentioning
confidence: 99%